The Study on the sociocultural profile of women working in a Brazilian nuclear area institution: Study on the sociocultural profile of women working in a Brazilian nuclear area institution - Ana Gabryele Moreira dos Santos; Priscila Santos Rodrigues; Karoline Feitoza Suzart; Nelida del Mastro (Brazilian Journal of Radiation Sciences, 2022)
RESUMO